THE CRISIS OF THE ROHINGYA AS A MUSLIM MINORITY IN MYANMAR AND UN RESPONSE TO THE ROHINGYA REFUGEES - Крупеня, І. (Навчально-науковий інститут міжнародних відносин КНУ імені Тараса Шевченка, 2022)
The purpose of this paper is to analyze the causes and consequences of the forced migration of the Rohingya Muslim minority from Myanmar to the countries of Southeast Asia. The Rohingya problem is considered as composed of various clusters of past and present human rights violations in Myanmar which has caused their forced migration to neighboring countries of ASEAN, such as Bangladesh, Malaysia, Indonesia, the Philippines and Thailand, on boats through the waters of the Malacca Strait and the Andaman Sea. This study analyzes the UN responses to manage and resolve the Rohingya problems as well. International initiatives for the introduction of the peace process and mediation services of China to resolve the conflict are studied.

Метою дослідження є аналіз причин та наслідків вимушеної міграції мусульманської меншини рохінджа з М’янми до країн Південно-Східної Азії. Вважається, що проблема народу рохінджа складається з різних кластерів: минулих і теперішніх порушень прав людини в М’янмі, що спричинило їхню вимушену міграцію до сусідніх країн АСЕАН, таких як Бангладеш, Малайзія, Індонезія, Філіппіни та Таїланд на човнах через води Малаккської протоки і Андаманське море. У статті також аналізується реакція та дії ООН щодо вирішення проблем народу рохінджа. Досліджено міжнародні ініціативи із запровадження мирного процесу та посередницькі послуги Китаю задля вирішення конфлікту.
КРИЗА БІЖЕНЦІВ РОГІНДЖА ЯК МУСУЛЬМАНСЬКОЇ МЕНШИНИ В М’ЯНМІ ТА РЕАКЦІЯ ООН НА ЦЮ ПРОБЛЕМУ